Kebiasaan Jajan, Diet Ketat, Indeks Masa Tubuh dan Persepsi Body Image pada Remaja di Tiga Kecamatan di Depok dan Bogor: Snacking Habits, Strict Diet, BMI, and Body Image of Adolescents in Three Sub-Districts in Depok and Bogor - Lina Agestika; Ratnayani Ratnayani (Amerta Nutrition, 2023)
Background: Body image is related to adolescent food preferences, which determine their nutritional status. Peri-urban areas might have different adolescents' snacking habits, strict diets, nutritional status, and body image. Objectives: This study aimed to analyze the association between adolescents' snacking habits, implementation of a strict diet, and nutritional status on their body image. Methods: This study used a mix-method, a combination of the quantitative and qualitative survey with a cross-sectional design. A total of 39 adolescents aged 15-18 who live in the peri-urban areas of Depok and Bogor were consecutively selected. The study was conducted in January 2022. Quantitative data include respondents' characteristics, body weight and height, snacking habits, and body image. Qualitative data collected were types of snacks, their reasons for buying snacks, and perceptions of ideal weight. Results: The nutritional status of the respondents was underweighted (5%), normal (92%), and overweight (3%), with snacking frequency 4-7 times/week (59%) with a weekly snacking expenditure of IDR 15,000 – 30,000 (49 %). As many as 23% of respondents performed a strict diet and perceived having a thin (21%) and fat (23%) body image. Adolescents with normal nutritional status were perceived as having fat (20.5%) and thin (15.4%) body image (p: 0,0215). There was also a relationship between diet (p: 0.0084) and weekly snacking expenditure (p: 0.0152) with body image, and there was no relationship between snacking frequency (p: 0.3123) and daily meal frequency (p-value=0.3972) with body image.  Conclusions: A wrong perception of body image from actual nutritional status can affect snacking habits and the implementation of a strict diet among adolescents.